Proteomic Analysis Reveals Different Involvement of Embryo and Endosperm Proteins during Aging of Yliangyou 2 Hybrid Rice Seeds - Zhang, Ying-Xue; Xu, Heng-Heng; Liu, Shu-Jun; Li, Ni; Wang, Wei-Qing; Møller, Ian M.; Song, Song-Quan (Frontiers in Plant Science, 2016)
Seed ageing is a process that results in a delayed germination, a decreased germination percentage, and finally a total loss of seed viability. However, the mechanism of seed ageing is poorly understood. In the present study, Yliangyou 2 hybrid rice (Oryza sativa L.) seeds were artificially aged at 100% relative humidity and 40°C, and the effect of artificial ageing on germination, germination time course and the change in protein profiles of embryo and endosperm was studied to understand the molecular mechanism behind seed ageing. With an increasing duration of artificial ageing, the germination percentage and germination rate of hybrid rice seeds decreased. By comparing the protein profiles from the seeds aged for 0, 10 and 25 d, a total of 91 and 100 protein spots were found to show a significant change of more than 2-fold (P<0.05) in abundance, and 71 and 79 protein spots were identified, in embryos and endosperms, respectively. The great majority of these proteins increased in abundance in embryos (95%) and decreased in abundance in endosperms (99%). In embryos, most of the identified proteins were associated with energy (30%), with cell defense and rescue (28%), and with storage protein (18%). In endosperms, most of the identified proteins were involved in metabolism (37%), in energy (27%), and in protein synthesis and destination (11%). The most marked change was the increased abundance of many glycolytic enzymes together with the two fermentation enzymes pyruvate decarboxylase and alcohol dehydrogenase in the embryos during ageing. We hypothesize that the decreased viability of hybrid rice seeds during artificial ageing is caused by the development of hypoxic conditions in the embryos followed by ethanol accumulation.